PERSEPSI PETANI TERHADAP TEKNOLOGI PENGOLAHAN PAKAN DI KECAMATAN KERINCI KANAN KABUPATEN SIAK - Susy Edwina; Evi Maharani (Indonesian Journal of Agricultural Economics, 2010)
The research was conducted in the village of Bukit harapan, District Kerinci Kanan, SiakRiau Province, aiming to find out the perception of farmers who have implemented theintegration of Cattle and Oil Palm (SISKA). The study lasted for 8 (eight) months,starting from March 2010. The study population was all farmers of the Joint AdvancedFarmers Group in the Village of Bukit harapan who have applied SISKA and feedprocessing technology. Sampling used census method of 7 members of the group.Sampling of non farmer groups of 15 people was carried out with the snowball method,which is an oil palm plantation farmers in the village of Bukit Harapan. Results showedperception of farmers of feed processing technology in the Joint Advanced FarmersGroup in the village of Bukit Harapan, District Kerinci Kanan, Siak Regency providesrelative advantages over the traditional way, with high fitness level, low level ofcomplexity (because the technology is simple), but somewhat difficult to start / appliedon a small scale, and easily observed in relatively quick time, through institutionalsupport for farmer groups in the formation of adequate venture capital and social capital.In general, the farmers perception of feed processing technology innovation is in goodcategory, so the technology worth to be disseminated to farmers by using groupapproach.